Representation and exceeding the powers of bodies of an entrepreneurial company: issues of theory and law application - V. H. Zhornokui (Law and Safety)
The article supports the view that acquisition of civil rights and obligations by a legal entity is conditioned, in particular, by its own bodies of will expression, and the ability to be independently liable with all its property is conditioned by the actual availability of such property which could be recovered if necessary.